"The Impact of Macroeconomic Factors on the Change of Residential Prices" The case study of Albania - Fationa Halili (International Journal of Applied Research in Management and Economics, 2023)
The housing market is a very important sector worldwide and occupies a significant part of their capital stock. Given that the economy is experiencing a difficult situation, because of the Covid-19 pandemic crisis, also based on the financial crisis of 2007-2008, their impact has been immediate in the change in house prices. Moreover, this paper will contain the investigation of some of the macroeconomic variables that affect housing prices in Albania. The study is built on econometric models, using bound test to understand what correlation relationship exists between GDP, inflation and mortgage rate and evaluating the "Autoregressive Distributive Lags" model in the short-term period, as well as looking at the perspective of a long-term period according to the "Vector Error Correction" (VEC) model. From the result obtained from E-views software, it is shown that depending on the time periods, the impact of these macro variables is different. If in the short term it seems that the impact of the mortgage rate is not a very substantial variable or inflation can have a negative impact, in long-terms is the opposite. To have a model that is as reliable and strong as possible, "battery" tests have also been analyzed to diagnose its constituent elements such as heteroskedasticity, autocorrelation, normality and the CUSUM / CUSUM square test for stability of the model. This paper applies to all areas, whose political implications can be found mainly for the bank, various investors or even policy makers, which may be the Bank of Albania, which should pursue policies to stimulate economic growth and show caution in the level of inflation created or setting the mortgage threshold.